Bla ma'i rnal 'byor Zla ba'i bdud rtsi bźugso - Byams-pa-ʼjam-dpal-dbaṅ-phyug (s.n., 1970)
In Tibetan; liturgical text on the worship of the tantric preceptor (gurupuja) directed to Ṅag-dbaṅ-nor-bu-bzaṅ-po (Lama Gulu), 1850-1934, founder of Tengboche Monastery.